Buffer Zone Mapping Konsep Shuttle Bus UTU untuk Mewujudkan Sustainable Green Transportation - Firzan, Firzan; Irfan, Irfan; Samsunan, Samsunan; Basrin, Defri; Yani, Deni Ilham (Jurnal Aplikasi Teknik Sipil, 2025)
UTU (UTU) is a state university in the western part of Indonesia, the province of Aceh, with 6,636 active students (2022) having the characteristics of a building that is integrated in the existing conditions and does not yet have public transportation facilities that serve student activities in the ±5KM buffer zone. Based on the daily pilot activity survey, more students live near campus and travel using private vehicles, walking and cycling, so the concept of implementing the shuttle bus is very helpful for students as a means of transportation to campus. This research uses qualitative and quantitative descriptive data analysis methods. The purpose of this study is to find out how much student response is to the concept of implementing shuttle bus services, carry out buffer zone mapping and desire lines at a ±5KM radius to find out potential zones and routes. The results of the study 93.5% of students strongly agreed with the implementation of the shuttle bus, 75.3% of students agreed to switch modes of transportation from private vehicles to shuttle buses. Based on the buffer zone mapping of the desire line results, there are 5 zones with the maximum movement potential, namely zone C (ADB 1 Housing) 1092 movements on the route Jln. Alue peunyareng-Jln. Pramuka.